Lengthening of the photoperiod influences sleep characteristics before and during total sleep deprivation in rat. (4th June 2018) - Sauvet, Fabien; Gomez‐Merino, Danielle; Dorey, Rodolphe; Ciret, Sylvain; Gallopin, Thierry; Drogou, Catherine; Arnal, Pierrick J.; Chennaoui, Mounir
Abstract: The photoperiod has been evidenced to influence sleep regulation in the rat. Nevertheless, lengthening of the photoperiod beyond 30 days seems to have little effect on the 24‐hr baseline level of sleep and the response to total sleep deprivation. We studied the effects of 12:12 (habitual) and 16:8 (long) light–dark photoperiods on sleep, locomotor activity and body core temperature, before and after 24 hr of total sleep deprivation. Eight rats were submitted for 14 days to light–dark 12:12 (lights on: 08:00 hours–20:00 hours) followed by total sleep deprivation, and then for 14 days to light–dark 16:8 (light extended to 24:00 hours) followed by total sleep deprivation. Rats were simultaneously recorded for electroencephalogram, locomotor activity and body core temperature for 24 hr before and after total sleep deprivation. At baseline before total sleep deprivation, total sleep time and non‐rapid eye movement sleep per 24 hr and during extended light hours (20:00 hours–24:00 hours) were higher (13% for total sleep time) after light–dark exposure compared with habitual photoperiod, while percentage delta power in non‐rapid eye movements and rapid eye movements were unchanged. Locomotor activity and body core temperature were lower, particularly during extended light hours (20:00 hours–24:00 hours). Following total sleep deprivation, total sleep time and non‐rapid eye movements were significantly lower after long photoperiod between 20:00 hours and 24:00 hours, and between 10:00 hours and 12:00 hours, and unchanged per 24 hr. The percentage delta power in non‐rapid eye movements was lower between 08:00 hours and 11:00 hours. Total sleep deprivation decreased locomotor activity and body core temperature after habitual photoperiod exposure only. Fourteen days under long photoperiod (light–dark 16:8) increased non‐rapid eye movements sleep, and decreased sleep rebound related to total sleep deprivation (lower non‐rapid eye movements duration and delta power). This may create a model of sleep extension for the rat that has been found to favour anabolism in the brain and the periphery.